P29 Reduced expression of Tim-3 renders Th1 and Th17 effector cells less amenable to T-reg control in autoimmune hepatitis. (6th September 2011) - Liberal, R; Mieli-Vergani, G; Vergani, D; Longhi, M S
Abstract : Introduction: In autoimmune hepatitis (AIH), CD4 effector immune responses are permitted by defective CD4 + CD25 + regulatory T-cells (T-regs). In murine studies apoptosis of Th1 effector cells is mediated by binding of T-cell-immunoglobulin-and-mucin-domain3 (Tim-3) on their surface to Galectin-9 (Gal9) expressed by T-regs. In AIH, Tim-3 is down-modulated on CD4 effector cells. Aim: To test the frequency of Tim-3 + cells within the Th1, Th2 and Th17 subsets and to evaluate whether Tim-3 expression by CD4 effectors affects their responsiveness to T-reg control. Method: 39 ANA/SMA + patients (23 females; median age: 13.9 years) and 16 healthy subjects (HS, 12 females; median age: 29.5 years) were studied. Cell phenotype was determined by cytofluorimetry using monoclonal antibodies to CD4, CD25 and TIM3. The frequency of cells positive for T-bet, GATA3 and RORC, transcription factors defining Th1, Th2 and Th17 cell subsets, was determined by intracellular staining. Proliferation of CD25 −, CD25 − Tim-3 + and CD25 − Tim-3 − target cells was assessed by 3 H-thymidine incorporation after 5-day co-culture with T-regs. Results: The frequency of Tim-3 + cells within the Th1 and the Th17 subsets was lower in AIH than in HS (Th1: 5.1±0.7 vs 13.6±1.7, p<0.001; Th17: 3.9±0.3 vs 8.2±1.1, p=0.02), while there was no difference for Th2 cells. In AIH, there was a negative correlation between the frequency of Tim-3 + cells and AST levels (r= −0.47, p=0.002) and a positive correlation between the frequency of T-bet + cells and AST levels (r=0.69, p<0.01). Addition of T-regs reduced cell proliferation by 26% (p=NS) in AIH and by 53% (p=0.007) in HS when undivided CD25 - cells were used as targets; by 23% (p=NS) and by 25% (p=NS) when Tim-3 − cells were the targets and by 47% (p=0.03) and by 62% (p=0.001) when the targets were Tim-3 + cells. Conclusion: In AIH, reduced frequency of Tim-3 within the Th1 and Th17 effector cell subsets renders them less prone to T-reg control, CD4 effector cell proliferation depending on the expression of Tim-3. T-bet expression characterises effector T-cells likely to mediate liver damage in AIH.